Study of intracellular anabolism of 5-fluorouracil and incorporation in nucleic acids based on an LC-HRMS method - Christelle Machon; Frédéric Catez; Nicole Dalla Venezia; Floriane Vanhalle; Laetitia Guyot; Anne Vincent; Maxime Garcia; Béatrice Roy; Jean-Jacques Diaz; Jérôme Guitton (Elsevier, 2021)
5-Fluorouracil (5-FU) is an anticancer drug extensively used for different cancers. Intracellular metabolic activation leads to several nucleoside and nucleotide metabolites essential to exert its cytotoxic activity on multiple cellular targets such as enzymes, DNA and RNA. In this paper, we describe the development of a method based on liquid chromatography coupled with high resolution mass spectrometry suitable for the simultaneous determination of the ten anabolic metabolites (nucleoside, nucleotide and sugar nucleotide) of 5-FU. The chromatographic separation was optimized on a porous graphitic carbon column allowing the analysis of the metabolites of 5-FU as well as endogenous nucleotides. The detection was performed on an Orbitrap® tandem mass spectrometer. Linearity of the method was verified in intracellular content and in RNA extracts. The limit of detection was equal to 12 pg injected on column for nucleoside metabolites of 5-FU and 150 pg injected on column for mono- and tri-phosphate nucleotide metabolites. Matrix effect was evaluated in cellular contents, DNA and RNA extracts for nucleoside and nucleotides metabolites. The method was successfully applied to i) measure the proportion of each anabolic metabolite of 5-FU in cellular contents, ii) follow the consequence of inhibition of enzymes on the endogenous nucleotide pools, iii) study the incorporation of metabolites of 5-FU into RNA and DNA, and iv) to determine the incorporation rate of 5-FUrd into 18 S and 28 S sub-units of rRNA.